A collection of fish leeches (Hirudinida: Piscicolidae) from Japan and surrounding waters, including redescriptions of three species - Furiness, Sharon; Williams, Julianne I.; Nagasawa, Kazuya; Burreson, Eugene M. (Journal of Parasitology, 2007)
Leeches were observed incidentally on fishes in collections made from 1975 to 2006 in Japan and surrounding waters, or from mariculture facilities or public aquaria in Japan. Seven species of leeches in 7 genera were collected - Crangonobdella maculosa, Johanssonia arctica, Limnotrachelobdella okae, Platybdella olriki, Stibarobdella bimaculata, Taimenobdella amurensis, and Trachelobdella livanovi. The transfer of Calliobdella livanovi to Trachelobdella is supported, and Trachelobdella livanovi and Taimenobdella amurensis are redescribed based on new specimens. Stibarobdella bimaculata is synonymized with Stibarobdella macrothela based on eyes, tubercle patterns, and sucker size ratios. Taimenobdella amurensis, C. maculosa, J. arctica, S. macrothela, and P. olriki are reported for the first time from Japan. New hosts are reported for L. okae, T. livanovi, S. macrothela, C. maculosa, J. arctica, and P. olriki. Stibarobdella moorei was not collected during this study, but a wellpreserved specimen collected in Japan was discovered in the Museum National d'Histoire Naturelle, Paris, France, and it allowed a redescription of this species. Stibarobdella loricata is synonymized with S. moorei based on tubercle patterns and the presence of papillae and a marginal fringe on the oral sucker.